2018
DOI: 10.1007/s11064-018-2654-0
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Trafficking of Homomeric and Heteromeric Kainate Receptors with Impaired Ligand Binding Sites

Abstract: Kainate receptors (KARs) are a subfamily of ionotropic glutamate receptors (iGluRs) mediating excitatory synaptic transmission. Cell surface expressed KARs modulate the excitability of neuronal networks. The transfer of iGluRs from the endoplasmic reticulum (ER) to the cell surface requires occupation of the agonist binding sites. Here we used molecular modelling to produce a range of ligand binding domain (LBD) point mutants of GluK1–3 KAR subunits with and without altered agonist efficacy to further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The GluK2 LBD K525E mutation led to creation of a hydrogen bond but no predicted observable thermodynamic effect was predicted (∆∆G = 0.06), shown in Supplementary Figure S4. However, a decrease in predicted positive electrostatic potential was observed over the ligand binding domain area of the GluK2 K525E variant (Supplementary Figure S5) and which could influence cell surface expression 47 . Taken together, in silico protein modeling analysis suggests that these three predicted damaging mutations could affect protein conformation, structural relationships or electrostatic potential.…”
Section: Resultsmentioning
confidence: 99%
“…The GluK2 LBD K525E mutation led to creation of a hydrogen bond but no predicted observable thermodynamic effect was predicted (∆∆G = 0.06), shown in Supplementary Figure S4. However, a decrease in predicted positive electrostatic potential was observed over the ligand binding domain area of the GluK2 K525E variant (Supplementary Figure S5) and which could influence cell surface expression 47 . Taken together, in silico protein modeling analysis suggests that these three predicted damaging mutations could affect protein conformation, structural relationships or electrostatic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Other protein reacting substances such as PKC (protein kinase C)-mediated phosphorylation and SUMOylation (small ubiquitin-related modifier) have been reported to have impacts on surface expression and endocytosis [ 54 ]. Moreover, molecular modeling and calcium imaging studies showed that the occupancy of both GluK2 and GluK5 ligand binding domains is required for the full activation of GluK2/GluK5 heteromeric KAR channels [ 55 ]. Of note, the non-canonical signaling of KARs which activates phospholipase C and PKC via a metabotropic G-protein dependent pathway, regulating neuronal excitability by inhibiting the slow afterhyperpolarization, neurotransmitter release, and glutamate receptor trafficking could potentially contribute to increased neuronal excitability [ 56 ].…”
Section: Subcellular Structure and Physiology Of Glutamate Receptorsmentioning
confidence: 99%
“…It has been shown that coexpression of GluK2 and GluK5 subunits yields functional heteromers with defined 2:2 stoichiometry next to GluK2 homotetramers (58). GluK5 homotetramers remain nonfunctional and do not traffic to the membrane (56)(57)(58)(59).…”
Section: Ubp-310 Antagonizes Gluk1 Homomers But Reduces Desensitizationmentioning
confidence: 99%